REHABILITATION AND ANASTAMOSY AFTER ILEOSTOMA IN NECROTIC ENTEROCOLITIS - Ochilov Rustam Ochilovich (World Scientific Research Journal, 2025)
Abstract. Necrotic enterocolitis (NEK) is a serious disease with high mortality, which is often found in premature and critically ill infants. In the late stages of the disease, the need for ileostomy is often necessary. Although this procedure is an important step in saving the child’s life, the subsequent rehabilitation process and restoration of the anastomosis are of great importance. After ileostomy, a child may experience fluid and electrolyte imbalance, difficulties with feeding, and a weakened immune system. Therefore, during the rehabilitation period, it is important to properly establish parenteral and enteral nutrition, prevent infections, provide special diets, and provide supportive therapy. In the next stage, intestinal continuity is restored through an anastomosis operation. For this process to be effective, the child must be brought to a complete clinical stable state. This study sheds light on the factors of complex rehabilitation and success of anastomosis after ileostomy in NEC.